2023
DOI: 10.4081/aiua.2023.11502
|View full text |Cite
|
Sign up to set email alerts
|

Does isotretinoin affect spermatogenesis in the long term? A rat model

Abstract: Objectives: Spermatogenesis, in which cell regeneration continues, can be affected by environmental, chemical, psychological factors or various diseases. There is conflicting information in the literature about the effect of isotretinoin, which is widely used in acne treatment, on testes and spermatogenesis. Therefore, we planned a rat study to evaluate the long-term efficacy of oral isotretinoin on testicular tissues and spermatogenesis. Materials and methods: The Group 1 (n = 6) 7.5 mg/kg/day and the Group 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Most studies focus on adult rats. In clinical practice, some authors, like Cirakoglu et al, [21], underlined the controversy and lack of consensus about whether isotretinoin has any effects on spermatogenesis. His study concluded that both high-dose and low-dose isotretinoin disrupted spermatogenesis; however, it did not affect the hypothalamic-pituitary-gonadal axis.…”
Section: Supplementation At a Young Agementioning
confidence: 99%
“…Most studies focus on adult rats. In clinical practice, some authors, like Cirakoglu et al, [21], underlined the controversy and lack of consensus about whether isotretinoin has any effects on spermatogenesis. His study concluded that both high-dose and low-dose isotretinoin disrupted spermatogenesis; however, it did not affect the hypothalamic-pituitary-gonadal axis.…”
Section: Supplementation At a Young Agementioning
confidence: 99%